New antimicrobial chitosan derivatives for wound dressing applications. (5th May 2016) - Dragostin, Oana Maria; Samal, Sangram Keshari; Dash, Mamoni; Lupascu, Florentina; Pânzariu, Andreea; Tuchilus, Cristina; Ghetu, Nicolae; Danciu, Mihai; Dubruel, Peter; Pieptu, Dragos; Vasile, Cornelia; Tatia, Rodica; et al.
Highlights: New sulfoanamide-chitosan derivatives have been synthesized and characterized. Sulfoanamide-chitosan derivatives membranes have been prepared and characterized. Chitosan derivatives membranes have improved swelling and biodegradation rate. Chitosan-sulfadiazine membrane has good antimicrobial effect and healing properties. Abstract: Chitosan is a non-toxic, biocompatible, biodegradable natural cationic polymer known for its low imunogenicity, antimicrobial, antioxidant effects and wound-healing activity. To improve its therapeutic potential, new chitosan-sulfonamide derivatives have been designed to develop new wound dressing biomaterials. The structural, morphological and physico-chemical properties of synthesized chitosan derivatives were analyzed by FT-IR, 1 H NMR spectroscopy, scanning electron microscopy, swelling ability and porosity. Antimicrobial, in vivo testing and biodegradation behavior have been also performed. The chitosan derivative membranes showed improved swelling and biodegradation rate, which are important characteristics required for the wound healing process. The antimicrobial assay evidenced that chitosan-based sulfadiazine, sulfadimethoxine and sulfamethoxazole derivatives were the most active. The MTT assay showed that some of chitosan derivatives are nontoxic. Furthermore, the in vivo study on burn wound model induced in Wistar rats demonstrated an improved healing effect and enhanced epithelialization of chitosan-sulfonamide derivatives compared to neat chitosan. The obtained results strongly recommend the use of some of the newly developed chitosan derivatives as antimicrobial wound dressing biomaterials.